Development of an inflatable solar dryer for improved postharvest handling of paddy rice in humid climates - Salvatierra-Rojas, Ana; Nagle, Marcus; Gummert, Martin; Bruin, Tom de; Müller, Joachim (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Rice is the staple food for more than three billion people worldwide. Although considerable progress has been made with respect to improved breeds and production practices, losses during postharvest handling remain considerable. Drying and storage of paddy are two key stages where management can be improved. For rice, grain moisture content of 14% prevents microbiological activity, while a level of about 12% minimizes quality losses over prolonged storage periods. Due to the need for simple and economical technologies, an inflatable solar dryer (ISD) was developed based on adaptations of the Hohenheim-type solar tunnel dryer. To form a drying tunnel, transparent polyethylene (PE) film attaches by zipper to a reinforced black polyvinyl chloride (PVC) film. To reduce heat loss, a flexible multilayer floor was used along the drying area. The tunnel does not need a substructure as it is stabilized adequately from pressure created by two axial flow ventilators. During experiments, paddy was spread on the floor and mixed with a special roller bar. The ISD has been evaluated for paddy in the Philippines during both rainy and dry seasons and was subsequently optimized. Sun drying and shade drying were carried out in parallel for comparison and product was evaluated for moisture content and quality in terms of milling recovery and head rice yield. Moisture content was reduced from 23% to 14% within 26-52 h of continuous operation during the rainy season and 16% to 14% within 4-26 h of drying during the dry season. In both seasons, the final moisture content of 12% was reached after prolonged drying periods. Quality was not found to be affected with respect to drying treatment. The ISD showed advantages over sun drying, despite longer drying periods.Keywords: paddy rice, postharvest handling, solar dryer, mobile dryer, collapsible dryer, Philippines DOI: 10.3965/j.ijabe.20171003.2444Citation: Salvatierra-Rojas A, Nagle M, Gummert M, de Bruin T, Müller J. Development of an inflatable solar dryer for improved postharvest handling of paddy rice in humid climates. Int J Agric & Biol Eng, 2017; 10(3): 269–282.